ENSINO SUPERIOR E SOCIEDADE BRASILEIRA: ANÁLISE HISTÓRICA E SOCIOLÓGICA DOS DETERMINANTES DA EXPANSÃO DO ENSINO SUPERIOR NO BRASIL (DÉCADAS DE 1960/70) - Barros, César Mangolin de (2008)
The work is a result of theoretical research, and historical documentary on Brazilian expansion of higher education in the decades of 1960 until mid-1970. Specifically, aimed to demonstrate how and in what form made the process of expansion of higher education and its crucial political, economical and social, and analyzing the social causes of the increased pressure for access to higher education. Thus, this assignment is based on the work of several Brazilian authors on higher education and on Brazilian social formation in the period, in addition to the analysis of documents and specific legislation on higher education. It concludes that the changes in Brazilian society from the mid of 1950 lead the middle classes, more than any other class to increase the pressure for access to higher education. Such pressure from middle classes will, in the political context opened by the military coup of 1964, gives the basic social student movement, which appears as the main focus of political contestation of the dictatorship. The expansion of higher education, which was in the process of university reform from 1968 and the following years, carried out by the military dictatorship, ruled administrative changes that were already present in the demands of the students, and already had been put into practice in institutions as the ITA and UNB while promoted private higher education, based on courses multiplication and establishments isolated, with the main intention of containing the student movement and prevent the passage of the middle classes to the field of the opposition, which helped the possible conquest of hegemony in Brazilian society.(AU)